What can we talk about, in which language, in what way and with whom? Sami patients’ experiences of language choice and cultural norms in mental health treatment - Dagsvold, Inger Johanne; Møllersen, Snefrid; Stordahl, Vigdis (International Journal of Circumpolar Health, 2015)
Source at https://doi.org/10.3402/ijch.v74.26952 . Background - The Sami in Norway have a legal right to receive health services adapted to Sami language and culture. This calls for a study of the significance of language choice and cultural norms in Sami patients’ encounters with mental health services. Objectives - To explore the significance of language and cultural norms in communication about mental health topics experienced by Sami patients receiving mental health treatment to enhance our understanding of linguistic and cultural adaptation of health services. Method - Data were collected through individual interviews with 4 Sami patients receiving mental health treatment in Northern Norway. A systematic text reduction and a thematic analysis were employed. Findings - Two themes were identified: (I) Language choice is influenced by language competence, with whom one talks and what one talks about. Bilingualism was a resource and natural part of the participants’ lives, but there were limited possibilities to speak Sami in encounters with health services. A professional working relationship was placed on an equal footing with the possibility to speak Sami. (II) Cultural norms influence what one talks about, in what way and to whom. However, norms could be bypassed, by talking about norm-regulated topics in Norwegian with health providers. Conclusion - Sami patients’ language choice in different communication situations is influenced by a complexity of social and cultural factors. Sami patients have varying opinions about and preferences for what they can talk about, in which language, in what way and with whom. Bilingualism and knowledge about both Sami and Norwegian culture provide latitude and enhanced possibilities for both patients and the health services. The challenge for the health services is to allow for and safeguard such individual variations within the cultural framework of the patients.